PENGARUH SUBSTITUSI AIR KELAPA MUDA DENGAN PENGENCER SITRAT KUNING TELUR TERHADAP MOTILITAS DAN PERSENTASE HIDUP SPERMATOZOA ANJING - Sulabda, I Nyoman; Puja, I Ketut (Buletin Veteriner Udayana; Vol. 2 No. 2 Agustus 2010)
The purpose of this study was to determine the effect of tender coconut water substitutionon egg yolk citrate diluent with different doses on local breeds dog sperm motility and livespermatozoa. Semen was manually collected. Progressive motility and percentage of livespermatozoa were evaluated under a microscope utilizing a drop of semen between awarmed glass slide and coverslip, both at a temperature of 38 0C. The percentage of motileand live spermatozoa were examined by counting 100 spermatozoa using the classificationof Christiansen (1984). Sperm viability was assessed by eosinnegrosin staining. The result showed that coconut water substitution has significant effect on the motility and livespermatozoa . Combination between the levels of coconut water in the egg yolk citratediluent could be applied as an alternative diligent instead of egg yolk diligent for dogsemen up to 75%.
Keywords: Coconut water, canine spermatozoa